Impact of obesity on oral contraceptive pharmacokinetics and hypothalamic-pituitary-ovarian activity - Edelman, Alison B (2009)
OBJECTIVE: This study was conducted to determine whether increased body mass index (BMI) affects oral contraceptive (OC) pharmacokinetics and suppression of hypothalamic-pituitary-ovarian (HPO) axis activity. STUDY DESIGN: Ovulatory reproductive-age women of normal (< 25 kg/m(2); n = 10) and obese (> 30 kg/m(2); n = 10) BMI received OCs for two cycles (prospective cohort). Subjects were admitted for two 48-h inpatient stays at the beginning and end of the hormone-free interval. Ethinyl estradiol (EE) and levonorgestrel (LNG) levels were evaluated during both inpatient stays. Gonadotropin pulsatility (FSH and LH) was measured during the second inpatient stay. Estradiol (E(2)) and progesterone (P) were measured daily during inpatient stays and twice per week in Cycle 2. RESULTS: BMI was greater in the obese, compared to the normal BMI group [37.3 kg/m(2) (SD 6.0) versus 21.9 kg/m(2) (SD 1.6); p < 0.05]. The LNG half-life was significantly longer in the obese group (52.1 ± 29.4 h versus 25.6 ± 9.3 h, p < 0.05) which correlated with a lower maximum LNG concentration on Cycle 2, Day 1 [1.9 ng/mL (SD 0.5) versus 2.5 ng/mL (SD 0.7)] and a longer time to reach steady-state (10 versus 5 days), in obese women. There were no significant differences in volume of distribution between groups. LH pulse parameters did not differ statistically between groups but trended towards greater HPO activity in the obese group. Additionally, more obese (6/10 versus 3/10 normal BMI, p > 0.05) women exhibited E(2) levels consistent with development of a dominant follicle, and P levels consistent with ovulation (2/10 versus 1/10) during Cycle 2. CONCLUSIONS: Compared to women of normal BMI, obese women exhibit differences in OC pharmacokinetics that are associated with greater HPO activity.